The Responsibility of Compesation Charge in Environmental Pollution for Consolidated Actor Companies - Fakhriah, Syahriati; Ardha, Dea Justicia; Rani, Febrina Hertika (Universitas Islam Negeri Raden Fatah Palembang, 2022)
The rise of pollution and environmental destruction due to human actions in the environment utilizing and even intentionally polluting or destroying the environment in people's lives. When a default occurs, companies as legal subjects are responsible for paying costs and interest in addition to compensation. They are also responsible for paying compensation if they conduct an illegal act.. The issue in this research How The Responsibility Of Compesation Charge In Environmental Pollution For Consolidated Actor Companies. The purpose of this study is to find out the form of responsibility of Compesation Charge in Environmental Pollution for Consolidated Actor Companies. The method used is Normative.The author's consideration of this issue leads to the conclusion that the special provisions of Article 122 of Law Number 40 of 2007 addressing Limited Liability Companies supersede the provisions of Article 87 paragraph (2), which are now general provisions. Therefore, Lex specialis derogat legi generali—the rule that special provisions take precedence over general laws—applies in this situation. As a result, the provisions of Article 122 of Law Number 40 of 2007 regarding Limited Liability Companies supersede those of Article 87 paragraph (2) of Law Number 32 of 2009 regarding Environmental Protection and Management.